Valve embolization during transcatheter aortic valve implantation: Incidence, risk factors and follow-up by computed tomography - Frumkin, David; Pietron, Malte; Kind, Andreas; Brand, Anna; Knebel, Fabian; Laule, Michael; Leistner, David M.; Landmesser, Ulf; Krackhardt, Florian; Sherif, Mohammad; Sündermann, Simon H.; Grubitzsch, Herko; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: In most cases of transcatheter valve embolization and migration (TVEM), the embolized valve remains in the aorta after implantation of a second valve into the aortic root. There is little data on potential late complications such as valve thrombosis or aortic wall alterations by embolized valves. Aims: The aim of this study was to analyze the incidence of TVEM in a large cohort of patients undergoing transcatheter aortic valve implantation (TAVI) and to examine embolized valves by computed tomography (CT) late after TAVI. Methods: The patient database of our center was screened for cases of TVEM between July 2009 and July 2021. To identify risk factors, TVEM cases were compared to a cohort of 200 consecutive TAVI cases. Out of 35 surviving TVEM patients, ten patients underwent follow-up by echocardiography and CT. Results: 54 TVEM occurred in 3757 TAVI procedures, 46 cases were managed percutaneously. Horizontal aorta (odds ratio [OR] 7.51, 95% confidence interval [CI] 3.4-16.6, p < 0.001), implantation of a self-expanding valve (OR 4.63, 95% CI 2.2-9.7, p < 0.01) and a left ventricular ejection fraction <40% (OR 2.94, 95% CI 1.1-7.3, p = 0.016) were identified as risk factors for TVEM. CT scans were performed on average 26.3 months after TAVI (range 2-84 months) and detected hypoattenuated leaflet thickening (HALT) in two patients as well as parts of the stent frame protruding into the aortic wall in three patients. Conclusions: TVEM represents a rare complication of TAVI. Follow up-CT detected no pathological findings requiring intervention.